Arabic Mawlid Poetry And Its Cultural-Spiritual Significance In Egypt And Tamil Nadu: Evolution And Contemporary Relevance - Zubair K M A Dr, Ahamed; Lebbai, Nahvi Muhiyadeen; Ali, M. Yasar Arafath; Hameed, A. Ahamed Shahul; Naina, K. Seyad Ahmed (Ijaz Arabi Journal of Arabic Learning, 2025)
Mawlid al-Nabi, the celebration of the birth of the Prophet Muhammad, has evolved into a cultural tradition in the spiritual, social, and artistic fabric of Muslim societies worldwide. This article explores the historical development and cultural significance of Mawlid, with a focus on poetic and creative expressions in Egypt and Tamil Nadu, India. It also highlights the role of Mawlid poetry in strengthening communal bonds, examines the integration of Sufism in shaping the form and content of Mawlid recitations, and its importance in spiritual reflection and communal worship. This study uses a qualitative, descriptive, and comparative approach. It involves textual analysis of Mawlid poetry and literary works, contextual historical studies, and cultural interpretation to understand the evolution and significance of Mawlid al-Nabi in the Egyptian and Tamil contexts. Through a literature review and analysis of key Mawlid works, including Qasidatul Witriyyah and Subuhana Mawlid, the study reveals that local cultural practices, poetic styles, and religious sentiments have shaped the celebration, fostering unity among diverse Muslim communities. The continued relevance of Mawlid in modern society, particularly through media and performance, is its adaptability and enduring significance. Mawlid is a multifaceted tradition that bridges religious devotion, artistic expression, and cultural identity, affirming its central place in Islamic heritage. This study reveals that Mawlid poetry has flourished in Egypt and Tamil Nadu, reflecting adaptations to local cultural, linguistic, and religious contexts. The study suggests that these works are essential expressions of spiritual devotion and cultural identity, fostering community cohesion. The study highlights the distinctive linguistic styles, poetic devices, and motifs used in the compositions, illustrating Islamic religious literature's rich diversity and creativity. These findings have significant implications for Arabic language teaching, as integrating Mawlid poetry into the curriculum can enhance student’s cultural awareness and appreciation of Arabic and Islamic heritage. Mawlid's poetry's spiritual and cultural relevance also provides a meaningful context that can motivate students, making language learning more engaging and authentic.